2013
DOI: 10.1364/josab.30.002059
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond filamentation in sapphire with diffractive lenses

Abstract: In this paper, we demonstrate novel properties in the phenomenology of supercontinuum generation in sapphire with diffractive lenses and provide a complete spatial, spectral, and temporal characterization of the so-generated pulses. Filament formation inside the sample is analyzed and related to the measured spectra, finding that clipping of the filament results in blueshifted spectra. For comparison, filament formation with refractive lenses is also examined, and the roles of diffraction and extension of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Figure 20(b) shows an example how the spectral intensity within certain spectral regions and the overall shape of the resulting SC spectrum is modified by varying the time delay between the co-filamenting fundamental and second harmonic pulses. An efficient control of the SC spectrum was also performed by changing the relative position of the focus in the nonlinear medium by means of diffractive optics [264,265] or by varying the spatial phase of the input beam with spatial light modulators [266,267]. Fine adjustment of the position of the nonlinear focus was demonstrated by varying the carrier envelope phase of a few-cycle input pulse [268].…”
Section: Control Of Supercontinuum Generationmentioning
confidence: 99%
“…Figure 20(b) shows an example how the spectral intensity within certain spectral regions and the overall shape of the resulting SC spectrum is modified by varying the time delay between the co-filamenting fundamental and second harmonic pulses. An efficient control of the SC spectrum was also performed by changing the relative position of the focus in the nonlinear medium by means of diffractive optics [264,265] or by varying the spatial phase of the input beam with spatial light modulators [266,267]. Fine adjustment of the position of the nonlinear focus was demonstrated by varying the carrier envelope phase of a few-cycle input pulse [268].…”
Section: Control Of Supercontinuum Generationmentioning
confidence: 99%
“…DLs have been shown to be a powerful tool for the spectral control of SC generation in bulk [31][32][33]. Here, we have demonstrated the dynamic control of the fringe visibility obtained by the interference between SC pulses generated in bulk media by using DMLs encoded into a SLM.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, it has been demonstrated [24] that when a femtosecond beam is focused with a diffractive lens, wavelength tunability in the SC signal can be achieved by simply changing the lens-sample relative distance. It was found that the depth at which the filament is formed is closely connected to the SC spectrum [27]. Based on this, the position of the filament, and thus the spectral content of the SC generated signal, could be controlled by slightly modifying the focal length of the DMLs and keeping the pulse energy constant.…”
Section: Resultsmentioning
confidence: 99%